Extraction and optimization of Citronella (Cymbopogon nardus) essential oil using solventless extraction technique - Farhana Binti Suman (School of Bioprocess Engineering, University Malaysia Perlis, 2013)
Essential oil is a valuable essence that is isolated from plant material using various techniques. Essential oil carries the aroma of the plant which it be extracted. Essential oil has their own usefulness for example to be used as in medicinal purpose, aromatherapy industry, pharmaceutical industry, as an insect repellent, and many more.Citronella oil is one of the examples of essential oil that have highly demand in the industry from time to time. The current techniques used in producing essential oil in the industry have their own advantages and disadvantages. Solventless extraction technique is a new technique that has been studied to produce essential oil with high yield, high quality, low cost, low time consuming, and environmental friendly. Optimization by using Response Surface Methodology through Central Composite Design (CCD) is required to study the optimum condition for this technique to produce high yield of essential oil, before it is able to be commercialize to the industry. The effect of temperature and time of extraction has been studied in this research. Through the study, the maximum essential oil produced by this technique is at 100C and 10 hours, that is 1.354%. The oil produced at this condition is then being analyzed by using Gas Chromatography Mass Spectrometry (GCMS) to identify the active compound inside the plant material. In order to compare the yield and quality of oil produced, solvent extraction method was also conducted in this experiment. The yield has been calculated and the oil has been analyzed by using gas chromatography, (GC). Based on the comparison between these two techniques, it is proved that essential oil produced by using solventless extraction technique is higher in quality compared to essential oil produced by solvent extraction technique.